2013
DOI: 10.1097/sap.0b013e31828587d3
|View full text |Cite
|
Sign up to set email alerts
|

The Plastic Surgery Match

Abstract: Plastic surgery continues to be a very competitive program to match into out of medical school. To analyze the match process, all applicants to our plastic surgery residency program in 2012 were surveyed. Our results showed that with matching into plastic surgery as the primary outcome measure, those who matched applied to more plastic surgery programs, received and accepted more interview invitations, were younger, were less likely to be foreign medical graduates, reported higher costs, had higher Step 1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 14 publications
1
60
2
Order By: Relevance
“…Although past studies have observed that individual applicants who matched into PRS applied to more programs, 1 our study suggests an increase in applications does not improve the overall chances of successfully matching. These results may be illustrated by the Prisoner’s Dilemma of game theory.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Although past studies have observed that individual applicants who matched into PRS applied to more programs, 1 our study suggests an increase in applications does not improve the overall chances of successfully matching. These results may be illustrated by the Prisoner’s Dilemma of game theory.…”
Section: Discussioncontrasting
confidence: 92%
“…Applicants are spending an average of $6,073 and up to $15,000 on applications and interview travel. 1 Meanwhile, residency program directors are also obligated to review a greater number of applications, over 2 or more interview dates, compounding an already substantial time commitment. In this study, we examine whether an increased number of applications confers a benefit to applicants.…”
Section: Purposementioning
confidence: 99%
“…In the group model, however, this was no longer significant. A review of applicants to plastic surgery programs similarly showed a trend towards favoring students with home plastic surgery programs, but it was not significant 13 . We recommend that medical students consider attending a highly ranked medical school or one with an Otolaryngology residency program if there is any interest in pursuing Otolaryngology when applying for medical school.…”
Section: Discussionmentioning
confidence: 98%
“…Surveys have included graduates of one state, 7 selected institutions, 2 a regional campus, 8 and applicants to specific specialties. 9 14 The two largest studies had response rates of 20% and 47% respectively. 2 , 7 Low response rates potentially increase the selection bias of surveying specific groups.…”
Section: Introductionmentioning
confidence: 99%